Consumer cash usage: A cross-country comparison with payment diary survey data - John Bagnall; David Bounie; Kim P. Huynh; Anneke Kosse; Tobias Schmidt; Scott Schuh; Helmut Stix (Deutsche Bundesbank, 2014)
We measure consumers' use of cash by harmonizing payment diary surveys from seven countries: Australia, Austria, Canada, France, Germany, the Netherlands, and the United States (conducted 2009 through 2012). Our paper finds important cross-country differences, for example, the level of cash usage differs across countries. Cash has not disappeared as a payment instrument, especially for low-value transactions. We also find that the use of cash is strongly correlated with transaction size, demographics, and point-of-sale characteristics, such as merchant card acceptance and venue.
Keywords: E41; D12; E58; 330; money demand; payment systems; harmonization; payment diaries; crosscountry comparison